Virginia at war, 1861 - Davis, William C., 1946-; Robertson, James I., Jr. (James Irvin), 1930-2019.; Virginia Center for Civil War Studies (Lexington : University Press of Kentucky, 2005)
More Civil War battles were fought on Virginian soil than on that of any other Confederate state. No state suffered more from invasion and occupation than the Old Dominion, and none witnessed as much of the war. Virginia's story of the Civil War stands unique among the Confederate States. Virginia at War, 1861 looks at Virginia on the eve of secession, detailing the activities of the convention that finally took the state out of the Union and explaining how Richmond became the capital of the new Confederate nation. Chapters in the book examine Virginia's private state army and its little-known.
The Virginia State Convention of 1861 / James I. Robertson, Jr. -- Land operations in Virginia in 1861 / Craig L. Symonds -- Confederate soldiers in Virginia, 1861 / Joseph T. Glatthaar -- A Navy Department, hitherto unknown to our state organization / John M. Coski -- Afro-Virginians : attitudes on secession and civil war, 1861 / Ervin L. Jordan Jr. -- Richmond becomes the capital / William C. Davis -- The Shenandoah Valley of Virginia / Michael Mahon -- The tarnished thirty-fifth star / C. Stuart McGehee -- Diary of a Southern refugee during the War, 1861 / Judith Brockenbrough McGuire.
Includes bibliographical references (pages 225-229) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Virginia -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- Politics and government -- 1861-1865.; Secession -- Virginia; Virginie -- Histoire -- 1861-1865 (Guerre de Sécession); Virginie -- Politique et gouvernement -- 1861-1865.; Sécession -- Virginie; HISTORY; HISTORY -- United States -- State & Local -- South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); Military campaigns; Politics and government; Secession; Virginia; Sezessionskrieg; Politik; Virginia; Amerikaanse burgeroorlog; Virginie (États-Unis) -- 1861-1865 (Guerre de Sécession); Virginie (États-Unis) -- Politique et gouvernement -- 19e siècle.; 1861-1865; History